2017
DOI: 10.1108/ijwhm-02-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment and gender-based violence in Tanzania’s public service

Abstract: Purpose The purpose of this paper is to explore the causes, forms, extent, and consequences of sexual harassment and sexual violence at public sector workplaces in Tanzania. Design/methodology/approach A total of 1,593 civil servants participated in the survey, which was conducted in the Mtwara Region of Tanzania. The quantitative data were complemented with the results from eight focus group discussions. Findings The study revealed that 21 percent of women and 12 percent of men had experienced sexual hara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Harassment within a hostile working environment includes conduct in the workplace that would be viewed as intimidating or hostile [ 2 ]. A wide range of individuals such as teachers, colleagues, supervisors, subordinates, and third parties could perpetrate this type of activity [ 3 ]. Within educational settings, some male academics have considered it their right to demand sexual favours in return for grades or career progression that falls in line with the ILO definition of hierarchical and gendered power relations within this context or in occupational settings [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Harassment within a hostile working environment includes conduct in the workplace that would be viewed as intimidating or hostile [ 2 ]. A wide range of individuals such as teachers, colleagues, supervisors, subordinates, and third parties could perpetrate this type of activity [ 3 ]. Within educational settings, some male academics have considered it their right to demand sexual favours in return for grades or career progression that falls in line with the ILO definition of hierarchical and gendered power relations within this context or in occupational settings [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 Sexual harassment may be perpetrated by different individuals, including teachers, colleagues, supervisors, subordinates and third parties. 3 In line with the ILO definition, the hierarchical and gendered power relations within occupational or educational settings have naturalised a sexual contract in which some male colleagues or academics consider it a right to demand sex with female juniors or students in return for career progression or grades. 6 Some studies, primarily from high-income settings, have shown that those who report experiencing sexual harassment in the workplace typically report decreased job satisfaction, 7 psychological distress including anxiety, anger and depression, 8 as well as physical distress such as weight loss, fatigue and even symptoms of post-traumatic stress disorder.…”
Section: Open Accessmentioning
confidence: 99%
“…2 Depending on the setting, sexual harassment can encompass a range of behaviours and practices of a sexual nature, such as unwanted sexual comments or advances, sexual jokes, displaying pictures or posters objectifying women, physical contact or sexual assault. 3 Sexual harassment is often experienced in the workplace or in educational settings and women are more likely to experience sexual harassment than men. 2…”
Section: Introductionmentioning
confidence: 99%
“…As insufficient laws and policies along with perceptions and attitudes force women to a weaker position, it is reasonable to digest that dominance of men causing women to an even worse situation. However, it is noteworthy to highlight that men also are sexually violated by both male and female employees in various work settings (Hershcovis et al, 2010;Taber, 2017;Vuckovic et al, 2017) and sometimes women do it against women as well (Dyer et al, 2019;Findley et al, 2014).…”
Section: Male Dominancementioning
confidence: 99%